Pragmatic deficits with syntactic consequences?: L2 pronominal subjects and the syntax–pragmatics interface - Rothman, Jason (Journal of pragmatics, 2009)
Contemporary acquisition theorizing has placed a considerable amount of attention on interfaces, points at which different linguistic modules interact. The claim is that vulnerable interfaces cause particular difficulties in L1, bilingual and adult L2 acquisition (e.g. Platzack, 2001; Montrul, 2004; Müller and Hulk, 2001; Sorace, 2000, 2003, 2004, 2005). Accordingly, it is possible that deficits at the syntax–pragmatics interface cause what appears to be particular non-target-like syntactic behavior in L2 performance. This syntax-before-discourse hypothesis is examined in the present study by analyzing null vs. overt subject pronoun distribution in L2 Spanish of English L1 learners. As ultimately determined by L2 knowledge of the Overt Pronoun Constraint (OPC) (Montalbetti, 1984), the data indicate that L2 learners at the intermediate and advanced levels reset the Null Subject Parameter (NSP), but only advanced learners have acquired a more or less target null/overt subject distribution. Against the predictions of Sorace (2004) and in line with Montrul and Rodríguez-Louro (2006), the data indicate an overuse of both overt and null subject pronouns. As a result, this behavior cannot be from L1 interference alone, suggesting that interface-conditioned properties are simply more complex and therefore, harder to acquire. Furthermore, the data from the advanced learners demonstrate that the syntax–pragmatics interface is not a predetermined locus for fossilization (in contra e.g. Valenzuela, 2006).